Effectiveness of Law Enforcement by Satreskrim Against Criminal Acts of Village Fund Corruption (Case Study at Rembang Police) - Pratama, Reynold Mifta; Gunarto, Gunarto (Jurnal Hukum Khaira Ummah, 2025)
Abstract. Corruption of village funds is a form of crime that is detrimental to state finances and hinders development at the village level. Law enforcement against this crime is the main responsibility of law enforcement officers, including the Criminal Investigation Unit (Satreskrim) in the Corruption Crime Unit (Tipikor). In the jurisdiction of the Rembang Police, the implementation of law enforcement by Satreskrim is an important focus considering several cases of misuse of village funds that have surfaced. This study aims to determine, examine, and analyze the effectiveness of law enforcement by Satreskrim against corruption of village funds at the Rembang Police, obstacles and solutions in law enforcement by Satreskrim against corruption of village funds at the Rembang Police and the concept of the effectiveness of law enforcement by Satreskrim against corruption of village funds in the future. The approach method used in this study is Sociological juridical. The specifications of this study are descriptive analytical. The data source used is primary data. While secondary data is obtained from literature study research consisting of primary legal materials, secondary legal materials, and testier legal materials. Based on the results of the study, it can be concluded that the effectiveness of law enforcement by the Criminal Investigation Unit against criminal acts of village fund corruption at the Rembang Police in general, the implementation of law enforcement by the Criminal Investigation Unit is carried out with systematic guidelines referring to the Criminal Procedure Code (KUHAP) and internal regulations of the Republic of Indonesia Police. Obstacles and solutions in law enforcement by the Criminal Investigation Unit against criminal acts of village fund corruption at the Rembang Police are limited personnel and technical expertise, dependence on state loss audit reports, local social and political pressure, low legal awareness of village officials, minimal participation and courage of the community to report. These obstacles are faced with several solutions, namely by increasing the competence and number of corruption investigators, strengthening coordination with internal government supervisory officers, increasing legal protection for reporters and witnesses, increasing legal education for village governments, and strengthening the supervision system based on community participation. The concept of the effectiveness of law enforcement by the Criminal Investigation Unit against criminal acts of village fund corruption in the future is by prioritizing improvements to the legal system, modern technology, and strengthening the capacity of the Criminal Investigation Unit. By connecting the theory of legal effectiveness, it is hoped that law enforcement can be more targeted, efficient, and fair, which will ultimately create more equitable social justice for all Indonesian people, especially rural communities.